SIFAT PEMESINAN SEMBILAN JENIS KAYU DARI NUSA TENGGARA BARAT (Machining properties of nine wood species originated from West Nusa Tenggara) - Bakir Ginoga (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
The quality of machining properties of nine wood species, i.e. gawil (Mangifera altissima Blanco.); sana (T erminalia bellerica Roxb.); jinarti (Symplocos brandisii Ket V.) ; tunjang gunung (Neonauclea schlecteri Merr. et Perry); bayur (Pterospermum javanicum Jungh.); klokos (Eugenia grandis Wight.); blahui (Bischoffia javanica Bl.); garu (Dysoxylum densiflorum (Bl.) Miq.); and bangsal (Engelhardtia spicata Lechen ex B1.), originated from natural forest in West Nusa Tenggara, has been investigated in air dried condition.The results revealed that the planing, moulding and sanding quality varies from good (II) to very good(I); turning quality generally good (II); while boring quality varies from very good(I)until verypoor classes (V).Keywords: Machining properties; wood species; natural forest; West Nusa Tenggara.